Process and Evaluation of Online Learning in the Introduction to Management Course of Logistics Engineering Study Program, Universitas Pendidikan Indonesia - Pebi Yuda Pratama (Journal of Logistics and Supply Chain, 2021)
Covid-19 Pandemic in recent years forces urgent application of online learning in all levels of education. The implementation of online learning, especially at the higher level of education, uses various kinds of learning media, including Zoom application, Google Classroom, Google Meet, Youtube, Quizizz, Whatsapp, and several other applications. Introduction to Management is one of the compulsories first semester courses for students of the Logistics Engineering Study Program, UPI. This study wants to know how the process and evaluation of online learning affect the overall education in introduction to management course. Observation and sociometry methods in the form of evaluation rubric was used to get the data needed regarding how the students interact with their group when they do assignments. The problems in online learning such as power outages, internet network problems, packets running out can be resolved by balancing the use of video conference and WhatsApp media. The distribution of the evaluation rubric given to students at the end of the lecture is better to know it earlier, so that cases of inactivity of one of the students in group assignments can be anticipated.